The psychological aspects of perinatal safety - Elena M. Savitskaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Recent years are marked by psychologists’, psychotherapists’, obstetricians’, gynecologists’ and pediatricians’ growing interest to practical applications of perinatal psychologists’ theoretical achievements. But so far most patients who need perinatal psychotherapy have been unaware of the opportunities to get it. Preparation for pregnancy and childbirth now chiefly consists in expectant parents’ health care and improvement of families’ material living conditions. There are, however, plenty of psychological factors that may tell on the child’s perinatal development and affect the child’s health. These are primarily the woman’s psychological readiness for her forthcoming pregnancy, motives for having a child, the gestational dominant, the pregnant woman’s psycho-emotional state, perinatal communication and interaction with the child. The child’s safe perinatal development requires expectant parents’ more active co-operation with all the specialists involved in the process.